2019
DOI: 10.3390/biom9090393
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Root Growth Inhibition by Salinity and Cadmium is Mediated by S-Nitrosative Modifications of ROS Metabolic Enzymes Controlled by S-Nitrosoglutathione Reductase

Abstract: S-nitrosoglutathione reductase (GSNOR) exerts crucial roles in the homeostasis of nitric oxide (NO) and reactive nitrogen species (RNS) in plant cells through indirect control of S-nitrosation, an important protein post-translational modification in signaling pathways of NO. Using cultivated and wild tomato species, we studied GSNOR function in interactions of key enzymes of reactive oxygen species (ROS) metabolism with RNS mediated by protein S-nitrosation during tomato root growth and responses to salinity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 96 publications
(147 reference statements)
0
7
0
Order By: Relevance
“…Recently, Wang et al (2017) have shown that Al‐induced NO production may mediate Al toxicity by activating NADPH oxidase to increase ROS generation in soybean roots. Likewise, several studies have revealed that GSNOR exerts an important role in ROS homeostasis under abiotic stresses (Gong et al, 2015; Jedelská et al, 2019; Rustérucci et al, 2007). In the present study, the gene expressions of RbohD and RbohF were depressed by NO scavenger cPTIO treatment, but were increased by GSNOR inhibitor N6022 which eliminated the ROS decrease caused by EBR (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wang et al (2017) have shown that Al‐induced NO production may mediate Al toxicity by activating NADPH oxidase to increase ROS generation in soybean roots. Likewise, several studies have revealed that GSNOR exerts an important role in ROS homeostasis under abiotic stresses (Gong et al, 2015; Jedelská et al, 2019; Rustérucci et al, 2007). In the present study, the gene expressions of RbohD and RbohF were depressed by NO scavenger cPTIO treatment, but were increased by GSNOR inhibitor N6022 which eliminated the ROS decrease caused by EBR (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we observed that the activity of APX was significantly increased in the roots of both Solanum spp. genotypes cultivated in agar medium supplemented with GSNO or GSNOR inhibitor N6022, which was associated with increased S-nitrosation of APX 40 . In this study, the increase of GSNOR activity induced by salinity and cadmium stress in S. habrochaites and subsequent lower levels of S-nitrosothiols resulted in decreased S-nitrosation status and decreased APX activity, in contrast to stress-induced down-regulated GSNOR activity in S. lycopersicum cv.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we observed that the activity of APX was significantly increased in the roots of both Solanum spp. genotypes cultivated in agar medium supplemented with GSNO or GSNOR inhibitor N6022, which was associated with increased S-nitrosation of APX 40 .…”
Section: S Protease Regulatorymentioning
confidence: 99%
“…These enzymes include superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), glutathione peroxidase (GSH-Px), and ascorbate peroxidase (APX). Cd induces ROS production by stimulating NADPH oxidase activity, replacing essential cations at specific binding sites, and inhibiting enzyme activity [ 147 ].…”
Section: The Mechanisms Of Plant Enrichment Of CDmentioning
confidence: 99%